2020
DOI: 10.1128/aem.00842-20
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Evaluation of New Hydroxymethylfurfural Oxidases for Furandicarboxylic Acid Production

Abstract: The enzymatic production of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxy-methylfurfural (HMF) has gained interest in recent years, as the renewable precursor of poly(ethylene-2,5-furandicarboxylate) (PEF). 5-Hydroxymethylfurfural oxidases (HMFOs) form a flavoenzyme family with genes annotated in a dozen bacterial species, but only one enzyme purified and characterized to date (after heterologous expression of a Methylovorus sp hmfo gene). This oxidase acts on both furfuryl alcohols and aldehydes being, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 42 publications
(77 reference statements)
1
31
0
Order By: Relevance
“…The oxidation of HMF and its derivatives makes Ma AAO quite interesting for application as biocatalyst in enzymatic synthesis of FDCA. While the chemical route to FDCA requires high temperature and pressure, organic solvents, and metal catalysts (Sajid et al 2018 ), some enzymes were shown to catalyze one or more of the individual reaction steps under mild reaction conditions without cosolvents (Carro et al 2015 ; Daou et al 2019 ; Dijkman and Fraaije 2014 ; Karich et al 2018 ; Mathieu et al 2020 ; Vinambres et al 2020 ). For example, 5-hydroxymethylfurfural oxidase (HMFO) from Methylovorus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation of HMF and its derivatives makes Ma AAO quite interesting for application as biocatalyst in enzymatic synthesis of FDCA. While the chemical route to FDCA requires high temperature and pressure, organic solvents, and metal catalysts (Sajid et al 2018 ), some enzymes were shown to catalyze one or more of the individual reaction steps under mild reaction conditions without cosolvents (Carro et al 2015 ; Daou et al 2019 ; Dijkman and Fraaije 2014 ; Karich et al 2018 ; Mathieu et al 2020 ; Vinambres et al 2020 ). For example, 5-hydroxymethylfurfural oxidase (HMFO) from Methylovorus sp.…”
Section: Discussionmentioning
confidence: 99%
“…With the explosive integration of biocomputational research, the comprehension of enzyme fundamentals [86] can lead to precise genetic manipulation of enzymes for more sustainable, reusable, and selective HMF oxidation. Specifically, the development of robust HMFO is a passionate research topic to boost the simplicity of HMF deep oxidation [87] . Furthermore, an abiotic electrode can be coupled with these useful enzymes to facilitate the oxidation of HMF electrochemically.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…GMC oxidoreductases were identified in ascomycetous and basidiomycetous fungi, plants, insects, and bacteria (Cavener 1992;Iida et al 2007;Martin et al 2020). Recently, hydroxymethylfurfural oxidases (HMFOs; EC 1.1.3.47) have been discovered which also belong to the GMC oxidoreductase family and oxidize aromatic primary alcohols, aldehydes, and thiols (Dijkman and Fraaije 2014;Ewing et al 2014;Vinambres et al 2020). While AAOs are secreted by fungi, HMFOs have been found in bacteria like Methylovorus sp.…”
Section: Occurrence and Gmc Superfamilymentioning
confidence: 99%
“…Recently, two other HMFOs from P. nitroreducens and Pseudomonas sp. strain 11/12A, both heterologously expressed in E. coli, were shown to catalyze oxidation of 5-HMF to up to 99% FDCA after 96 h (Vinambres et al 2020). Carro and coworkers found that PeAAO expressed in E. coli also catalyzed the conversion of 5-HMF to FFCA, but no subsequent oxidation of FFCA to FDCA was detected.…”
Section: Production Of Bio-based Precursors For Polymersmentioning
confidence: 99%